Giant water scavenger beetles Hydrophilus subgenus Dibolocelus (Coleoptera: Hydrophilidae) from Mexico with description of two new species - Arce-Pérez, Roberto; Arriaga-Varela, Emmanuel; Novelo-Gutiérrez, Rodolfo; Navarrete-Heredia, José L. (Zootaxa, 2021)
The Hydrophilus (Dibolocelus) Bedel species from Mexico and adjacent areas are treated on the basis of the study of 142 adult specimens and published data. Two new species are herein recognized and described: H. (D.) nucleoensis Arce-Pérez & Arriaga-Varela sp. nov. from Mexico, Guatemala and Nicaragua, H. (D.) pseudovatus Arce-Pérez & Arriaga-Varela sp. nov. from Mexico. Three already known species are re-described and their geographical distribution is updated, H. (D.) ovatus Gemminger & Harold and H. (D.) pollens Sharp and H. (D.) violaceonitens Jacquelin du Val, a species resurrected as distinct to H. (D.) smaragdinus. Hydrophylus (D.) cf. purpurascens (Régimbart) is also redescribed but their identity is questionable. The lectotype of H. (D.) pollens Sharp is designated. Within Mexico, the state with the highest known diversity is Veracruz with five species. A key to the species of Hydrophilus (Dibolocelus) from Mexico and Central America is provided.